Staying within or leaving the apprenticeship training system? : Revisions of educational choices in apprenticeship training - Bessey, Donata [Verfasser]; Backes-Gellner, Uschi [Verfasser] (My University, 2015)
"The decision to revise an educational choice has hardly been analyzed in previous research. Dropping out is only one possible choice, and we distinguish between dropping out (leaving the apprenticeship system) and changing or upgrading (staying within the apprenticeship system) as three possibilities to revise an educational decision, using a dataset that consists of apprentices who have dissolved their apprenticeship contract. We analyze the determinants of leaving apprenticeship training using competing risks models. Dropout decisions seem to be driven by financial considerations such as financial distress, but local labor market conditions seem to have no effect on them. Our findings underline the importance of distinguishing between the different choices instead of focusing exclusively on dropping out." (Authors' abstract, BIBB-Doku)

"Dieses Working Paper analysiert Revisionen von Ausbildungsentscheidungen in der dualen Ausbildung. Im Gegensatz zu früherer ökonomischer Forschung analysieren wir nicht nur Abbruchentscheidungen, sondern beziehen explizit auch andere choices nach der Auflösung eines Ausbildungsvertrages ein. In Anlehnung an frühere Arbeiten von Neuenschwander (96, 98, Neuenschwander et al. 99) unterscheiden wir nach Auflösung eines Ausbildungsvertrages zwischen Abbruch (dropout), Wechsel (change) und Rückkehr ins allgemein bildende Schulsystem (upgrade). Die empirische Analyse wurde unter Verwendung eines deutschen Datensatzes aus dem Jahr 2002 durchgeführt. Als Kontrollgruppe verwenden wir die Auszubildenden, deren Lehrvertrag aufgrund eines Bankrotts ihres Ausbildungsbetriebes aufgelöst wurde, und nehmen an, dass sie ihre Ausbildung ohne dieses Ereignis abgeschlossen hätten." (Autorenreferat, BIBB-Doku)
Vorab veröffentlicht u.d.T. "Dropping out and revising educational decisions: Evidence from vocational education" (Economics of Education Working Paper Series ; 0040)
Keywords: G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); I 2.2.1 Westeuropa; Ausbildungsabbruch; Ausbildungswahl; Ausbildungsentscheidung; Schweiz